Evaluating the Effect of Fertilization and Substrate Volumetric Water Content on Compact Tomato and Pepper Plants - Michael Fidler; Celina Gómez (HortTechnology)
Interest in compact vegetable plants for home gardening is increasing, but the production guidelines for these new crops are limited. Our objective was to characterize the effects of fertilizer use and substrate volumetric water content (VWC) on growth, quality, and yield of compact tomato and pepper plants. During a production phase, ‘Siam’ tomato and ‘Basket of Fire’ pepper were grown in a greenhouse for 22 days and 44 days, respectively, using 4-inch containers. Plants received water-soluble fertilizer once per week or tap water only and relied on the fertilizer starter charge in the substrate (electrical conductivity = 1.0 mS·cm−1). Plants were irrigated to container capacity when the substrate VWC reached 0.15, 0.30, 0.45, or 0.60 m3·m−3. During the postproduction phase, plants were allowed to wilt to assess the time required to reach different wilting stages or were transplanted into 8-inch containers, top-dressed with controlled-release fertilizer, and grown to harvest to evaluate carryover treatment effects. Our results showed that limiting the fertilizer application during production can have a larger effect on plant growth and yield than restricting VWC when the substrate is brought back to container capacity after each irrigation event. For example, plants of both species irrigated with only tap water during the production phase were shorter, had less biomass, and generally produced less fruit compared to plants that received fertilizer. In contrast, shoot height and shoot dry weight of tomato were the only two growth variables affected by VWC, and peppers were mostly unresponsive to differences in VWC. Although plants irrigated with only tap water during production had lower chlorophyll concentrations than those of plants that were fertilized, they quickly greened after receiving a single dose of fertilizer solution, suggesting that using a residual fertilizer strategy before shipping may help increase plant greenness when height-control treatments that induce chlorosis are used. Furthermore, wilt progression was slower in plants of both species irrigated with only tap water during the production phase, likely because of their smaller size that limited water demand. During the postproduction phase, the only differences in growth and yield were measured in pepper plants; fertilized plants were larger and produced more fruit compared to plants irrigated with only tap water during the production phase. Based on our results, growers should limit their fertilizer use when trying to produce compact vegetable plants, possibly relying only on the fertilizer starter charge incorporated into the substrate during short production cycles. However, reducing irrigation frequency may not have an effect on height and overall growth if plants are watered thoroughly each time.